A thermochromic poplar-based tetradecyl ester/methyl composite encapsulated with PEG400–SiO2 (PS-R-PTC) for improving thermal energy storage. Issue 17 (14th April 2023) - Tong, Yanqiang; Zou, Weihua; Sun, Delin; Wang, Zhangheng
Abstract : A R-PTC had been prepared in previous study by compositing tetradecyl ester, methyl red and poplar wood. For improving the heating storage ability, a PS-R-PTC was prepared by encapsulated R-PTC with PEG400–SiO2 in this work. Abstract : Thermochromic wood is an important research direction for wood modification in recent years, and a red poplar-based thermochromic composite (R-PTC) had been prepared in our previous study by compositing a mixture of phase change reagents (tetradecyl ester: C28 H56 O2 and methyl red: C15 H15 N3 O2 ) and full poplar wood. In order to improve the heating storage ability of R-PTC and encapsulating phase change reagents to prevent leakage, a new R-PTC composite (PS-R-PTC) was prepared by encapsulated R-PTC with polyethylene glycol 400 (PEG400)–SiO2 in this work. Compared to the original R-PTC samples, the cell walls of PS-R-PTC were not significantly changed by the SiO2 film and we also found that PS-R-PTC with PEG400 (90%)–silica solutions (10%) mixture had better heat storage performance and PS-R-PTC (90%) has better enthalpy change value (R-PTC: 43.01 J g −1 ; PS-R-PTC (90%): 71.82 J g −1 ). The PS-R-PTC can show the function of thermal energy storage, which is used in wooden buildings and can be a feasible insulating material for reducing thermal energy losses and hence reducing energy usage. In PS-R-PTC, SiO2 combines with the –OH of the R-PTC and the –OH of PEG400 (HO(CH2 CH2 O) n H), and these –OH lose hydrogen ions too.